Sifat sintered body keramik alumina pada ukuran partikel yang direduksi - Ade Indra (Retii, 2020)
Alumina sintered bodies (Al2O3), in the form of pellets, have been made by varying the size of particles. The initial particles were sieved on a 200-270 mesh (53-74 μm). The other sizes were refined using a centrifugal hammer mill and then sieved to obtain particles retained on the 270 mesh (> 54 μm) and the 400 mesh (37-53 μm), and those passed the 400 mesh (<37 μm). Polyvinyl alcohol (PVA) liquid as a binder was added into each of these size variations. The process of mixing alumina with PVA (alcohol as a diluent) was carried out for 2 h in a rotary drum with a ceramic ball in it. The mixture was dried at room temperature for 48 h to remove the alcohol. The mixture was smoothed again using a rotary drum for 2 h with a ceramic ball in it. Green bodies were made by uniaxial pressing method at a pressure of 100 MPa. The sintering process was carried out by preheating at a temperature of 700oC with a holding time of 1 h to eliminate PVA, and then the temperature was increased to 1200oC with a holding time of 2 h. During the sintering, the heating rate was maintained at 5oC/minute. The physical characteristics of the alumina sintered bodies were determined by testing the linear shrinkage, density, and microstructure characterization. Density increased with decreasing particle size, from 2.096 gr/cm3 to 2.140 gr/cm3 with an increase in relative density of 2%. The results showed a change in physical properties along with the reduction in the size of the alumina particles.